Netherlands Vaccine Diplomacy Towards Indonesia During Covid-19 Pandemic - Muawal, Fakhri Sabiq; Sari, Deasy Silvya (Universitas Airlangga, 2023)
Vaccine diplomacy is diplomacy that uses vaccines as the main tool of diplomacy. The Covid-19 pandemic presents an opportunity for vaccine producing countries and producing countries to conduct vaccine diplomacy. The Netherlands as a vaccine producing country has made Indonesia one of the targets for vaccine diplomacy. This research aims to explain the instruments and strategies used by the Netherlands in conducting vaccine diplomacy against Indonesia during the Covid-19 Pandemic. This research uses a qualitative method with secondary data in the form of books, journal articles, news, and document reports on the websites of the Netherlands Government and Indonesian Government institutions, as well as the results of interviews from the Ministry of Foreign Affairs of the Republic of Indonesia. the analysis technique used is thematic data. The findings from this research are that the Netherlands Government uses collaborative instruments with the More Formal Collaborative Instruments approach which was raised by the interaction of various international actors such as countries, international organizations and multinational vaccine manufacturing companies.